Comparison of Outside Versus Inside Brachial Plexus Sheath Injection for Ultrasound‐Guided Interscalene Nerve Blocks. (29th December 2015) - Maga, Joni; Missair, Andres; Visan, Alex; Kaplan, Lee; Gutierrez, Juan F.; Jain, Annika R.; Gebhard, Ralf E.
Abstract : Objectives: Ultrasound‐guided interscalene brachial plexus blocks are commonly used to provide anesthesia for the shoulder and proximal upper extremity. Some reviews identify a sheath that envelops the brachial plexus as a potential tissue plane target, and current editorials in the literature highlight the need to establish precise and reproducible injection targets under ultrasound guidance. We hypothesize that an injection of a local anesthetic inside the brachial plexus sheath during ultrasound‐guided interscalene nerve blocks will result in enhanced procedure success and provide a consistent tissue plane target for this approach with a reproducible and characteristic local anesthetic spread pattern. Methods: Sixty patients scheduled for shoulder surgery with a preoperative interscalene block for postoperative pain management were enrolled in this prospective randomized observer‐blinded study. Each patient was randomly assigned to receive a single‐shot interscalene block either inside or outside the brachial plexus sheath. Results: The rate of complete motor and sensory blocks of the axillary nerve territory 10 minutes after local anesthetic injection for the inside group was 70% versus 37% for the outside group ( P < .05). At all measurement intervals beyond 10 minutes, however, neither group showed a statistically significant difference in complete sensory blockade. The incidence rates of transient paresthesia during needle passage were 6.7% for the outside group and 96.7% for the inside group ( P < .05). Conclusions: Except for faster onset, this prospective randomized trial did not find any advantages to performing an interscalene block inside the brachial plexus sheath. There was a higher incidence of transient paresthesia when injections were performed inside compared to outside the sheath.